Love and violence : the vexatious factors of civilization - Melandri, Lea (SUNY Series in Contemporary Italian Philosophy Ser., 2019)
In this book, the Italian feminist thinker Lea Melandri argues that systemic violence against women has deep psychoanalytic roots. Drawing inspiration from the work of Freud and the psychiatrist and psychoanalyst Elvio Fachinelli, along with feminist practices of consciousness-raising, Melandri demonstrates how male dominance and female subservience are established by society through a binary and oppositional understanding of sex and gender. This understanding--and the oppression and violence against women that results--is inscribed in the psyches of both men and women, and is replicated anew from generation to generation. Melandri analyzes women in media, politics, philosophy, and literature to show how this plays out, and calls for awareness of these deep psychic structures and expectations formed within the dynamics of society and primary family relations.00Transl. from Italian by Antonio Calcagno.